2023
DOI: 10.3390/sym15020469
|View full text |Cite
|
Sign up to set email alerts
|

Topological Phase Transitions Driven by Sn Doping in (Mn1−xSnx)Bi2Te4

Abstract: The antiferromagnetic ordering that MnBi2Te4 shows makes it invariant with respect to the combination of the time-reversal and primitive-lattice translation symmetries, giving rise to its topologically nontrivial nature and a number of fundamental phenomena. At the same time, the possibility to control the electronic and magnetic properties of this system can provide new effective ways for its application in devices. One of the approaches to manipulate MnBi2Te4 properties is the partial substitution of magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Several studies [29][30][31][32][33] have demonstrated the synthesis of these crystals and confirmed the absence of additional substitution defects, as in the case of s substitution of Sb for Bi atoms.…”
Section: Introductionmentioning
confidence: 66%
“…Several studies [29][30][31][32][33] have demonstrated the synthesis of these crystals and confirmed the absence of additional substitution defects, as in the case of s substitution of Sb for Bi atoms.…”
Section: Introductionmentioning
confidence: 66%
“…The observed decrease in the band gap, culminating in an apparent zero gap with increasing Ge concentration, and the formation of a plateau with a minimum band gap in the concentration range of 45-55%, followed by a transition to the electronic structure of Mn-doped GeBi 2 Te 4 (at 90%), is consistent with previously reported data in the literature. This pattern has been observed both in systems where Mn atoms are replaced by Ge atoms 37,38 , as well as for substitutions with other Group IV elements such as Sn 36 and Pb 39 . However, the underlying reason for the formation of the minimum band gap plateau remains unclear.…”
Section: (B)mentioning
confidence: 75%
“…However, there is another possibility of modulating the energy gap at the DP and reaching the TPT point through the partial replacement of Mn atoms with IV-group elements (Ge, Sn, Pb) [36][37][38][39][40][41][42] . In Refs [36][37][38] , it was shown that when Mn is replaced by Ge, Sn, or Pb atoms in the Mn 1−x A x Bi 2 Te 4 (A = Ge, Sn, Pb) compounds, the bulk band gap decreases with an increase in the concentration of the substituting atoms. The gap decreases to practically zero at substituting element concentrations of 40-50%, with a possible transition from the topological state to the Weyl semimetal (WSM) state.…”
Section: Introductionmentioning
confidence: 99%
“…The criteria for the presence of a topological state is the inversion of the valence and conduction bands [ 1 ]. For MnBi Te , it appears as a domination of the contribution of the Bi states at the top edge of the valence band, and of the Te states at the bottom edge of the conduction band [ 19 , 23 ]. Figure 3 e–h shows the calculated dispersion dependencies for different concentrations of Ge, in which the colour shows the difference in contributions of the Te states and Bi states (red and blue, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…In this context, the other effective approach for altering the value of the energy gap involves the substitution of transition metal (Mn) atoms with non-magnetic elements. Specifically, elements such as Sn, Pb, and Ge have been investigated as potential substitutes for Mn due to their ability to form the desired ternary compounds, including SnBi Te [ 18 , 19 ], PbBi Te [ 20 ], and GeBi Te [ 21 , 22 ], which possess crystal structures similar to MnBi Te . Experimental findings have revealed that the replacement of Mn with either Pb [ 23 ], Sn [ 24 , 25 ] or Ge [ 26 , 27 ] not only reduces the magnetic moments of the system, but also induces variation in the band structure due to the changes in orbital composition of valence and conduction bands.…”
Section: Introductionmentioning
confidence: 99%